Estimation of actual evapotranspiration by numerical modeling of water flow in the unsaturated zone: a case study in Buenos Aires, Argentina - Cesanelli, Andrés (2009)
A method is presented to estimate actual evapotranspiration (ETA) from potential evapotranspiration (ETP) by numerical modeling of water flow in the unsaturated zone. Water flow is described by the Richards equation with a sink term representing the root water uptake. Evaporation is included in the model as a Neumann boundary condition at the soil surface. The Richards equation is solved in a one-dimensional domain using a mixed finite element method. The values of ETA are obtained by applying a water stress factor to ETP to account for soil moisture changes during the simulation period. The proposed numerical model is used to estimate ETA in an experimental plot located in a flatland area in Buenos Aires (Argentina). Numerical results show that the proposed model is a useful tool for evaluating evapotranspiration under different scenarios.